Roles and Contribution of Viet Nam Civil Society and NGO Toward Social Welfare: Challenges and Opportunities for Middle-Income Countries - MSc. Do Van Trai (Philippine Social Science Journal, 2025)
Following Vietnam’s 2015 reclassification as a Middle-Income Country and the subsequent decline in international aid, this paper investigates the capacity of civil society to address social needs, contrasting Vietnamese governance models with American philanthropic traditions. Utilizing a literature review and qualitative interviews, the study identifies a significant cultural divergence: while the American model is bolstered by a robust culture of charity, Vietnamese society prioritizes inward-looking extended family support and views social well-being as the government's primary responsibility. Consequently, charitable giving in Vietnam remains situational rather than systemic. The findings suggest that for Vietnamese NGOs to fill the service gap left by withdrawing aid, the nation must cultivate a domestic culture of philanthropy and trust in civic institutions. Ultimately, this research underscores the challenges of shifting from state-centric to community-led welfare frameworks, advocating for policies that strengthen non-state actors in emerging economies.